Advances in International Environmental Politics
XVI, 403 p.
Keywords: This book provides authoritative and up-to-date research for anyone interested in the study of international environmental politics. It demonstrates how the field of international environmental politics has evolved and identifies key questions, topics and approaches to guide future research.